El uso de las tic en la atención al cliente en la empresa Maplas de la ciudad de Latacunga - Chiluisa Villacis, Erick Alexander (2022)
The current research work is focused on determining the TIC use tools for customer service, which will be developed in the MAPLAS enterprise from Latacunga city, for effect was applied as first point a topic scientific-technical foundations, where will be covered related topics to the research topic, which allow providing necessary information for the aims development and fulfillment, On the other hand, it was also make a qualitative approach methodology, based onto and action research design, due to this allows to solve problems with the relation to topic, involving a group or community in the decisions that take for data analysis. This case, said group, MAPLAS enterprise members from Latacunga city, with a 15 people total. The instrument for using in the study will be the survey, whose aim is to establish the necessary TIC tools for customer service in the MAPLAS enterprise from Latacunga city. The beneficiaries will be the MAPLAS enterprise members, as well as its collaborators and users. The research is feasible to perform, because currently enterprises around the world have been forced to train in the different technological tools use for the development most their processes, especially, to improve customer service, due to he/she is the first contact that has, with consumers and potential customers, that is why it is the utmost importance to streamline processes, through the use these technologies and use them into an organizational context. As for the results of the research project, we obtained a verification of the probable possibilities that the company has in terms of TIC to implement in its method of customer service and allow technological interaction with different users, where three specific purposes were developed, starting with the search for bibliographic information verified in terms of TIC used for customer service, on the other hand the identification of technological tools within the company MAPLAS was performed and finally the proposal of TIC tools necessary for the organization such as: Facebook, WhatsApp, Web Page, Instagram, YouTube, Tik Tok and email whose purpose is to improve the quality of customer service by providing greater efficiency and technological automation of processes.